Persuasion in Messages - Laura Gorham; Ricky Telg; Tracy Irani (EDIS, 2013)
Specific contextual cues are added to media messages that persuade people to think one way or another about an issue and influence their actions. In this publication, you will learn the different ways that the mass media use persuasion and how persuasion encourages the audience to change their attitudes or behavior. This 3-page fact sheet was written by Laura Gorham, Ricky Telg, and Tracy Irani, and published by the UF Department of Agricultural Education and Communication, July 2013.